Universal Design for Learning and Diversity Attention: A Look from the Perceptions and Skills of Teachers - Alcívar Pincay, Gloria Anabel; Romero Salcedo, Josselyn Nicole; Zambrano Vélez, Vanessa (Journal of Ecohumanism, 2024)
The Universal Design model for learning provides a pathway to curriculum from a responsive approach to diversity. It is a real and applicable option to promote and enable the learning of all student bodies, but its application is conditioned to the competence level of the teacher. The purpose of this research is to know the teacher competence skills on the application of the three principles of Universal Design for learning. This work is a mixed descriptive cross sectional investigation, where 123 teachers from Manabí-Ecuador participated, same ones that belong to private, fiscal and fiscomisional educational institutions. The instrument used to measure teachers’ perception of Universal Design for Learning -Perception of Universal Design for Learning. It was applied by survey means and the information collected was complemented with focus group. The results allowed us to confirm that teachers have an adequate perception and skills to apply the principles of UDL, however, there are also training needs to strengthen the learning processes and participation of all students, with emphasis on competence skills to attend to the disability-derived diversity.